Curación Digital y Género en la Ciencia de la Información acceso y preservación - Jorente, Maria José Vicentini (Editora Oficina Universitária, 2022)
The world of presences is simulated, presented and represented in the digital medium. In the context of digital-virtual communication, and from the recent transformations in their supports, the multimodal collections of information pass to a state in which the access of informational subjects to information can be facilitated and expanded. In such a universe, the information and data represented need conceptual and technical treatments that respect the nature and particularities of the media and the languages that pass through them. In addition, being processed in a fragile medium such as digital, encoded information for electronic media also requires procedures and care aimed at its integral preservation. In Information Science, the set of continuous and iterative procedures intended to satisfy the demands for attention to optimize access and preservation is called Digital Curation: a complex of processes that go from initial design and conceptualization to metadata designation. , the evaluation of decisions to preserve or discard, the transformation, access, exchange and re-evaluation of digital objects. In gender-related issues, the need for Digital Curation of information presented in electronic media becomes urgent, given the dramatic facts that worry about the lack of information, or misinformation, in the multiple territories covered by the concept. In them, the information must be processed with the sociocultural purpose of creating strategies and instruments to overcome the innumerable challenges and injustices present.